Program Kemitraan Masyarakat Stimulus Kelompok Penjahit Pakaian di Desa Sungai Bali Kecamatan Pulau Sebuku Kabupaten Kotabaru Provinsi Kalimantan Selatan - Dayat Ikhsan Hajati; Taufik Rahim (Abdihaz: Jurnal Ilmiah Pengabdian pada Masyarakat, 2020)
Community Partnership Stimulus Program of Clothing Tailor Group in Sungai Bali Village, Sebuku Island District, Kotabaru Regency, South Kalimantan Province The problems faced by partners are: 1) Equipment and production equipment are still limited so that it takes a long time to fulfill large orders; 2) The equipment and production equipment are still very simple, which hinders the production process; 3) Inadequate place for display and stock storage; 4) The partner has never made a business financial report so that the partner cannot measure the development of his business so far; 5) Marketing is still very limited and passive where buying and selling is only waiting for the buyer to come to the house; 6) Promotional activities have never been carried out so that the product is only known to the community in the village; 7) The absence of a business name board so that prospective buyers from other villages is difficult to find partner business places. This community service program aimed to help partners overcome problems in the aspects of production and business management. The method or approach applied was discussion, training, mentoring, and adding the business equipment and equipment to motivate partners to achieve business success. The results and outcomes achieved were 1) Partners received additional production equipment such as portable electric sewing machines, new manual sewing machines, and storefront cabinets for product stock storage and name boards/signs; 2) Partners got training and assistance in making notes or financial reports, marketing management, and business correspondence; and 3) Partners could improve skills, product quality, product quantity, product types, production capacity, assets, and business income.